Sporthorse performance testing in eventing by own and progeny performance - Mezei, Anita; Posta, János; Mihók, Sándor (Acta Agraria Debreceniensis, 2012)
The aim of the study was to evaluate the Hungarian Sporthorse population based on eventing competition performance. The database contained the results of 792 horses and 449 riders between 2000 and 2006. The eventing results were gathered from Hungary and other European countries. Blom transformed ranks were used to evaluate the sport performance.Three models were fitted to the Blom scores. Evaluating all the competition categories at the same time weighted Blom scores were used according to the difficulty of the category. The linear mixed model included fixed effects for age, sex, breeder, owner, location, year; and random effects for animal and rider. Horses from the database were judged by their own performance, and stallions were investigated by performance of their progenies on the basis of descriptive statistics of Blom scores and weighted Blom scores. Breeding values of eventing performance were predicted. To improve the reliability of breeding values, more progenies should be used in eventing competitions.